2021
DOI: 10.3389/fcvm.2021.636152
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Perspectives of Sodium-Glucose Co-transporter 2 Inhibitors in Heart Failure

Abstract: Heart failure (HF) is a common complication or late-stage manifestation of various heart diseases. Numerous risk factors and underlying causes may contribute to the occurrence and progression of HF. The pathophysiological mechanisms of HF are very complicated. Despite accumulating advances in treatment for HF during recent decades, it remains an intractable clinical syndrome with poor outcomes, significantly reducing the quality of life and expectancy of patients, and imposing a heavy economic burden on societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 142 publications
0
16
0
2
Order By: Relevance
“…The novel antidiabetic agents, SGLT2 inhibitors, have been gradually reconsidered as an important class of medications for heart failure, being recommended for their beneficial impact in patients with type 2 diabetes patients and multiple cardiovascular risk factors or heart failure with reduced ejection fraction [ 11 ]. The current clinical guidelines for the management of heart failure are concentrated on a triple neurohormonal blockade, including beta-blockers, angiotensin-converting enzyme inhibitors (ACEIs), or angiotensin receptor blockers (ARBs), and mineralocorticoid receptor antagonists with specific recommendations based on the patientā€™s comorbidities [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The novel antidiabetic agents, SGLT2 inhibitors, have been gradually reconsidered as an important class of medications for heart failure, being recommended for their beneficial impact in patients with type 2 diabetes patients and multiple cardiovascular risk factors or heart failure with reduced ejection fraction [ 11 ]. The current clinical guidelines for the management of heart failure are concentrated on a triple neurohormonal blockade, including beta-blockers, angiotensin-converting enzyme inhibitors (ACEIs), or angiotensin receptor blockers (ARBs), and mineralocorticoid receptor antagonists with specific recommendations based on the patientā€™s comorbidities [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…In 1998, Oyama et al concluded that the impaired nitric oxide and oxidative stress pathways are responsible for cytokine-induced left ventricle (LV) dysfunction, and impact various cells, including endotheliocytes, vascular smooth muscle cells, infiltrating inflammatory cells, and cardiomyocytes [ 15 ]. Based on these pathophysiological mechanisms, anti-inflammatory and anti-cytokine therapies could be considered beneficial, although the clinical trials have not significantly improved the survival of patients with HF [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations